Relationship Between Violence and the Myth of Nation-Building: Exploring the connection between violence and nation-building in Indian writing (Journal of Advances and Scholarly Researches in Allied Education, 2012)
The partition of the India is a trauma in which India wasarbitrarily and forcefully divided. Modern writers of Indian descent areconstantly looking backward at this traumatic experience to explore therelationship between violence and the myth of nation-building. The dialecticsof violence, particularly characterizing the partition of the sub-continent,indeed exercised many a creative soul to articulate an artistic response to thelife event. The contours of this creative endeavour, in fact, parallel themultiple manifestations of this phenomenon in actuality that constantly andwith an ever increasing intensity explodes through the fluid and yetuncrystallised socio-cultural and political matrix of India. Writing narrativesof partition, in a sense, have almost become an obsession with the writers ofsouth-Asian descent. It also becomes inevitable to rememorize the past whicheither they have personally experienced or heard about it through family loreand legends. The present paper has focus on exploring the connection betweenviolence and the construction of a nation, and the ways in which the intrusionof public violence into private homes and neighborhoods became constitutive ofthe partition, with a special emphasis on the artistic reconstruction of theexperience dealt with the partition in Indian writing in English.